Antioxidant peptides produced from unexplored marine resources - Cunha, Sara A. (2021)
The sea contains about one half of the global biodiversity, thereby being a good source for novel compounds of interest, such as bioactive peptides. Mussels are consumed and appreciated over the world, although commercialized mussels are pre-selected before being delivered for sale, so small or broken mussels are discarded. Microalgae are photosynthetic organisms, easy to cultivate since they do not require cultivable land. The microalgae used in this work are produced in a company in which the CO2 generated in the production of cement is injected to microalgae growth tubes transforming it in oxygen, resulting in a decrease of CO2 emission. The chosen species, Chlorella vulgaris and Nannochloropsis oceanica, have interesting protein content, making them a promising sustainable protein source. Discarded mussels from the specie Mytilus galloprovincialis, supplied by a national mussel trading company, and the microalgae grown up with CO2 generated from cement production, were used to produce water soluble extracts rich in proteins and bioactive peptides, showing potential to the development of sustainable industrial alternatives, promoting new perspectives for a circular economy. Four extracts were produced and analysed: Mussel_Sub, hydrolysed with subtilisin (1.5%,3h); Mussel_Cor, hydrolysed with corolase (3%,3h); Chlorella, hydrolysed with acetic acid (0.5%,1h), cellulase (5%,2h) and subtilisin (3.9%;2h); and Nannochloropsis, hydrolysed with cellulase (5%,2h) and subtilisin (1.7%,5h). The protein content was determined by Kjeldahl and the antioxidant activity by ORAC and ABTS assays. The Chlorella extract showed 44.71±1.75% protein, 462.83±39.37 (ORAC) and 76.12±7.53 (ABTS) μmol TE/g. Nannochloropsis showed 31.01±0.27% protein, 361.32±49.29 (ORAC) and 68.07±6.97 (ABTS) μmol TE/g. Mussel_Cor showed 48.00±0.15% protein, 389.50±0.29 (ORAC) and 62.76±8.88 (ABTS) μmol TE/g; Mussel_Sub showed 45.23±0.14% protein, 485.62±60.65 (ORAC) and 66.11±2.35 (ABTS) μmol TE/g. The enzymatic hydrolysis of marine species may allow to produce extracts rich in proteins and antioxidant peptides useful for industrial applications, contributing to the valorisation of these species and to a circular economy, since mussel commercialization generates waste and microalgae can transform CO2 from other industries to O2, reducing the environmental impact.